Therapeutic interventions: an Islamic perspective - Rahman, Mohammad Tariqur; Nazer, Reeza; Brown, Lindsay; Ahmed Shogar, Ibrahim Adam; Bouzenita, Anke Iman (Islamic Medical Association of North America, 2008)
Disease and its healing in most of the therapeutic strategies are mainly based either on physical or metaphysical aspects. Therapeutic strategies in Islam, on the other hand, are based on a combination of spiritual, psychological, and material means. It is, therefore, important to analyze current therapeutic strategies according to the Qur’an and Sunnah and their relation to other medical models, as many options aiming at better health outcomes are now being used throughout the world. This paper examines how the guidelines and principles of the Qur’an and Sunnah may contribute to the understanding and evaluation of different therapeutic interventions. A successful activation of the Islamic therapeutic model and its furtherance apart from the use of limited therapeutic strategies on the individual level can take place only within a reactivation of an authentic Islamic way of life.